Innovative solutions for enhancing the fire resistance of slim-floor beams: Thermal experiments. (February 2020) - Albero, V.; Serra, E.; Espinós, A.; Romero, M.L.; Hospitaler, A.
Abstract: Slim-floor beams have attracted the attention of designers in the last decades, owing to their ability for supporting intermediate loads without increasing the floor thickness. However, the behaviour of this type of beams at elevated temperatures has not been well understood yet. This paper presents the results of an experimental campaign carried out at the testing facilities of the Universitat Politècnica de València, Spain, where a series of slim-floor configurations were exposed to elevated temperatures into an electrical furnace. These tests had the novelty of considering different slim-floor beam typologies, as well as alternative ways for thermal protection, such as using intumescent coating, stainless steel or lightweight concrete into different cross-section parts. The test results were used to validate a finite element thermal model which allows for a detailed analysis of the cross-section thermal behaviour and the assessment of different ways to improve the slim-floor beam fire performance. The temperature results were subsequently imported into a computer code developed by the authors where a non-linear procedure was applied to obtain the plastic bending capacity of the cross-section at elevated temperatures. These final results reveal the different thermal performance of the analysed configurations and are used as a basis for providing design recommendations for future slim-floor developments. Highlights: This paper presentsan experimental campaign where slim-floor beams were exposed to elevated temperatures into a furnace. These tests consider alternative ways for thermal protection, such as using intumescent coating or stainless steel. An effective way to improve the fire capacity consists of acting at the bottom plate in order to delay the temperature rise.